Non Specific and Specific Parameter Standardization of Banana Peel (Musa paradisciata Sapientum) and Andrographis Paniculata - Pusmarani, Jastria; Putri, Risky Juliansyah; Dewi, Citra; Purwono, Setyo; Ikawati, Zullies (Universitas Muhammadiyah Surakarta, 2019)
Purpose: The aim of this study is to standardize the methanol extract of banana peel (Musa paradisciata sapientum) and ethanolic extract of Andrographis Paniculata and Phytochemical screening of banana peel extract and Andrographis PaniculataMethodology: Standardization of the extract conducting with two parameters, they are specific and nonspecific parameters.Results: Content of water solvent of banana peel as many as 47.8% and as many as 35.79% in Andrographis Paniculata. Phytochemical screening result reveals that banana peel extract contains saponin, polyphenol, tannin, flavonoid, and terpenoid. Andrographis Paniculata extract contains alkaloid, steroid, terpenoid, flavonoid and saponin. Non-specific parameter can be observed based on water content, total ash content, non-soluble acid ash content and drying losses. Water content of methanol extract of banana peel as many as 8.47% and Andrographis Paniculata leaves as many as 7.91%. The result of total ash content of banana peel as many as 17.99% and Andrographis Paniculata leaves as many as 17.23%. Ash content of insoluble acid of banana peel as many as 3.15% and Andrographis Paniculata leaves as many as 5.10%. The result of drying loss determination of the extract of plantain peel is 9.37% and sambiloto leaves is8.82%.Applications/Originality/Value: Based on specific and non-specific standardization parameter assay which consist of methanol extract of banana peel and Andrographis Paniculata leaves meet the standardization of quality.